Stubbskörd : från modell till verklighet - Cagner, Gustav (SLU/School for Forest Management, 2011)
In the near future we need to reduce the greenhouse gas emissions significantly for the benefit of the environment around us. The European Union has de-manded a variety of climate and energy goals to be achieved by year 2020, the “20-20-20” targets. With these aims, The European Union means that we must reduce our emissions from fossil fuels and instead increase our renewable fuels. With stump harvest in the forest it’s possible to increase the use of renewable fuels and reduce our emissions from fossil fuels. The main purpose of this study is to answer the economic question: “Is it profitable to harvest stumps for the land owner”? In this report economic calculations are made for three areas which have been stump harvested. On these three areas, two different models were used to test if they could be used to predict the cost for stump harvest. The first model was developed by Mats Nylinder (1977) and the other model was developed by Johan Karlsson (2007). Both models worked well in this study and gave good result on comparison with the real invoice for the stump harvest. In conclusion areas lo-cated near heating stations and with good overall conditions for stump harvest can generate a good profit for the land owner.